International Hotel Chains in Montenegro – Focus on Ramada Hotel Podgorica - Djurasevic, Silvana; Kavaric, Andrea (Turizam, 2018)
International hotel chains have been present in the Montenegrin market for the past 13 years, but their inﬂuence on hospitality industry, as a branch, has only been strong in the last fve years. The frst hotel, which belongs to a hotel chain, came in 2004 by opening the Iberostar Bellevue Hotel in Becici. Today, there are eight branded hotels in Montenegro. The purpose ofthe research in this paper will be the contemporary trends in hospitality industry and their impact on the Montenegrin market. Research results suggest that although the share of branded hotels is small, the brand’s strength makes them dominant on the market and allows them the position of the demand generator and partially the oﬀer creator. Furthermore, new trendshave brought changes in the quality of service, application of standards, the creation of hotel products, sales and other essential issues for the hotel operation. A special review was given to the Ramada Hotel Podgorica, whose appearance on the capital city market strengthened and facilitated the opening of new branded hotels, such as Hilton Podgorica and Center Ville Hotel. Also, Ramada’s business analysis has helped signifcantly in highlighting the contribution of this and other branded hotels to the establishment of a modern hotel business in Montenegro